Effects of job stress and emotional labor on depression in call-center workers - Kim, Jung Im (Edelweiss Applied Science and Technology, 2024)
The purpose of this study was to investigate the effects of job stress and emotional labor on depression among call center workers. Data collection was conducted from October 2 to October 30, 2023. The subjects were 175 workers at a large IT call center located in Seoul, Korea. Data was analyzed using SPSS version 23.0. As for data analysis, differences in job stress, emotional labor, and depression were analyzed using t-test and ANOVA. Pearson's correlation coefficient was used to determine the correlation between job stress, emotional labor, and depression. Finally, multiple regression analysis was conducted on factors affecting depression. As a result of this study, the factors affecting call center workers' depression were the number of family members living together (t=-2.650, p=0.009), job stress (t=3.743, p<0.001), and emotional labor (t=2.064, p=0.041), (F=10.306, p<.001). In other words, the greater the number of call center workers' family members living with, the lower the level of depression, the higher job stress and the higher the emotional labor, the higher the level of depression. In conclusion, workplaces should conduct a full survey on the level of job stress and emotional labor to reduce the level of depression among call center workers. In addition, measures are needed to reduce job stress, and depending on the results, professional counseling and healing programs are needed for workers who complain of mental illness.